Kurikulum Kultural Berbasis Tradisi Islam Nusantara di Pondok Pesantren Putra Miftahul Mubtadiin Ar Ridlo Krempyang Tanjunganom Nganjuk - Ibad, Irsyadul; Arifin, Imron (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2025)
This research, titled Cultural Curriculum Based on Nusantara Islamic Tradition at Pondok Pesantren Putra Miftahul Mubtadiin Ar Ridlo Krempyang Tanjunganom Nganjuk, aims to explore the implementation of a curriculum based on Nusantara Islamic traditions in the educational process at Pondok Pesantren Putra Miftahul Mubtadiin Ar Ridlo. This study uses a qualitative approach with a case study method to understand how this curriculum is applied and how local cultural values are integrated into the learning process. Data was collected through participatory observation, in-depth interviews with the pesantren leaders, teachers, and students, as well as documentation. The findings show that this cultural curriculum serves as an important tool in shaping students' character, instilling nationalism, independence, love for the homeland, and appreciation for Nusantara Islamic traditions. The implementation of this curriculum also aligns with the spirit of religious moderation promoted by the Ministry of Religious Affairs of the Republic of Indonesia. Thus, this pesantren not only serves as a center for religious education but also as a place for the preservation and development of Nusantara Islamic traditions that are relevant to the social and cultural context of Indonesia